Grade-11 Students’ Conceptual Understanding of Chemical Reaction Rate from Learning by Using the Small-Scale Experiments - Supasorn, S.; Wuttisela, K.; Moonsarn, A.; Khajornklin, P.; Jarujamrus, P.; Chairam, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
This study aimed to investigate grade-11 students’ conceptual understanding of chemical reaction rate through 5E inquiry approach in which they were asked to explore data for answering the engaged question using the small-scale syringe-vial experiment (SSVE) and elaborate their understanding using the AR interactive Particulate-level Visualization (ARiPV). The two-tier diagnostic conceptual test and semi-structured interview questions served as the data collection instruments. Thirty-three grade-11 students cooperated in the series of four 2-hour 5E learning activities for a total of 8 hours. Dependent samples T-test analysis showed that the mean score of the postconceptual test (mean 29.77, S.D. 6.77, 66.16%) was statistically greater than that of the preconceptual test (mean 11.68, S.D. 10.14, 25.96%) at the significance level of 0.05. Their actual gain was 40.20% and their normalized gain was 0.54, a medium increase. The majority of them moved from the less correct category, Partial Understanding with Specific Misunderstanding (PMU, 43.03%), to the more correct category, Partial Understanding (43.84%). The semi-structured interview showed that the 5E inquiry technique using SSVE in conjunction with ARiPV was entertaining and successful in identifying and enhancing their understanding. This demonstrated that this integrated intervention can encourage students to shift their conceptual understanding of reaction rate to the more advantageous categories.